Improving the Economy of the Home Furniture Industry in Sugerkidul Village - Jember through Appropriate Technology - Misto; Endhah Purwandari; Artoto Arkundato; Wenny Maulina; Arry Y. Nurhayati (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2023)
Furniture (chairs, beds, sideboards and so on) are items needed by every household that potential to be cultivated as a livelihood. Some of the basic materials for making furniture products are available locally (village) and some come from the city. Techniques for making furniture products such as how to make wooden frames, cut furniture cloth or leather, sew furniture fabrics, and the process of assembling and combining them into a furniture product must be owned by furniture workers, in order to open a furniture business. In addition to the technical skills that must be possessed, the required equipment such as tools, sewing machines and so on must also be owned for this furniture business to be successful. Some of the difficulties of Jelbuk furniture entrepreneurs are that they do not have enough skills to sew and do not have a sewing machine. If there is sewing work, it is always given to another party whose existence is 20 km from Jelbuk. This is what makes Jelbuk entrepreneurs less economically empowered. Therefore, the purpose of carrying out this activity is to provide guidance on sewing techniques and procurement of sewing machines as an alternative solution for these furniture entrepreneurs. This activity was carried out in several stages, namely 1) procuring sewing machines that were tailored to the needs of making a furniture product, 2) providing guidance on sewing techniques, and 3) training on techniques for making fashion furniture products according to consumer tastes. Guidance on sewing techniques is given starting from getting to know the sewing machine and its characteristics as well as sewing guidance to make a simple product to the details. The results of the community service activities are enough to help improve the ability of sewing techniques so that all pron products can be done at their own place without having to be given to other parties, so that the completion is faster and more cost efficient. The guidance process is still given for 3 months until it is completely independent. The ability of furniture entrepreneurs increases, the settlement process is faster, the number of consumers increases and will ultimately increase the income of furniture entrepreneurs in Suger Kidul Village, Kec. Jelbuk, Kab. Jember.